2018
DOI: 10.1080/10253866.2018.1462174
|View full text |Cite
|
Sign up to set email alerts
|

Kitchen concerns at the boundary between markets and consumption:agencingpractice change in times of scarcity (Husmodern, Sweden 1938–1958)

Abstract: This paper investigates practice dynamics in kitchens situated at the boundary between markets and consumption. The kitchen is conceptualized as a market-consumption junction, a space where multiple concerned actors in markets and consumption come to shape, and get shaped by, the practices in the kitchen. Drawing upon archival research of the Swedish household magazine Husmodern (1938-1958), this study traces two matters of concern in and around the kitchen: the scarcity of resources in food markets and the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Matters of concern make the boundaries visible between the marketized place and the place-identity (see Stigzelius et al, 2018), while CSPs aim to realign them at a nexus of marketization. Expanding the work of Castilhos and Dolbec (2018), a nexus of marketization refers to a place where the marketized place and place-identity align.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matters of concern make the boundaries visible between the marketized place and the place-identity (see Stigzelius et al, 2018), while CSPs aim to realign them at a nexus of marketization. Expanding the work of Castilhos and Dolbec (2018), a nexus of marketization refers to a place where the marketized place and place-identity align.…”
Section: Discussionmentioning
confidence: 99%
“…Matters of concern can emerge and concretize in place when it is threatened in some way (Maclaran and Brown, 2005). While prior research has identified the importance of matters of concern and how they shape markets (e.g., D'Antone et al, 2017;Geiger et al, 2014;Stigzelius et al, 2018), we know surprisingly little about how CSPs emerge to address and negotiate matters of concern from place (Bitzer & Glasbergen, 2010;Finch et al, 2017;Gospodini, 2020). Such oversight is problematic given the often negative connotations around marketization of places (Castilhos & Dolbec, 2018;Guthey et al, 2014), such as overcrowding and commodification (MacCannell, 1973;Namberger et al, 2019;Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-existing spatial concepts – site, place, territory, region, scale, network – have increasingly been used across marketing theory and economic geography to explain the broader organisation and politics of markets (see, for example Berndt & Boeckler, 2011 ; Castilhos et al, 2017 ; Alvarez León et al, 2018 ; Ashton & Christophers, 2018 ; Hall, 2018 ; Castilhos & Dolbec, 2018 ; Vicdan & Hong, 2018 ; Lloveras et al, 2018 ; Roux et al, 2018 ). In market studies, where everyday performativity is emphasised through a focus on practice, the spatiality of markets is implicitly suggested through discussion of ‘context’ and ‘distribution’ (Araujo, 2007 ; Finch & Geiger, 2010 ; Kjellberg & Helgesson, 2006 ; Stigzelius et al, 2018 ). We build on and add subtlety to these contributions by introducing the concept ‘spatio-market practice.’ This concept sees the spatial dimensions of market making folded inside the practices of market actors.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Finch and Geiger ( 2010 ) argue that it is through the performance of practices that actors “help disentangle goods and services in a market space” (p. 237). Looking at the bounding of socio-material arrangements, Stigzelius et al, ( 2018 , p. 347) further conceptualise the kitchen as a market-consumption junction, “where multiple concerned actors in markets and consumption come to shape, and get shaped by […] practices in the kitchen.” Here, the kitchen is conceptualised as “an abstract space of political negotiations” and “a concrete place where different actors and artefacts come together” (Stigzelius et al, 2018 , p. 348). Together, these studies suggest that market making is very much a spatial affair, linked with the performance and ordering of multiple connected and situated socio-material market practices.…”
Section: Marketing Market Geographies and Spacementioning
confidence: 99%
“…Previous research highlights this complexity in the context of product categories (Rosa et al 1999), market categories (Navis and Glynn 2010), music genres (Anand and Peterson 2000) and geographical boundaries (Clark 1994). As discussed by Stigzelius et al (2018) the conceptual blurriness also affects academic discussions, where conceptions of markets vary significantly across different traditions and in some cases make meaningful discussions on the topic difficult. Moreover, practical and academic conceptions of markets and market boundaries are to some extent communicating vessels.…”
Section: Framing Market Boundariesmentioning
confidence: 99%